Respuesta :
Answer:
[tex]\frac{1}{6}(-10x-4)[/tex]
Step-by-step explanation:
To solve this problem you must apply the proccedure shown below:
1. You have that she substituted [tex]x=2[/tex] into the simplified expression and the result was -4.
2. Therefore, if you substitute [tex]x=2[/tex] into all the expressions shown in the options, you will see that the result of the expression [tex]\frac{1}{6}(-10x-4)[/tex] is -4, as you can see below:
[tex]\frac{1}{6}(-10(2)-4)=\frac{1}{6}(-24)=-4[/tex]
answer:
[tex]\frac{1}{6} [-10x-4][/tex]
Step-by-step explanation: